2016
DOI: 10.7553/81-2-1563
|View full text |Cite
|
Sign up to set email alerts
|

Academic libraries’ role in Research Data Management Services: a South African perspective

Abstract: Research Data Management (RDM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 8 publications
2
64
0
3
Order By: Relevance
“…As a result, current RDM-related literature tends to report on investigative surveys that have been conducted, pilot projects that have taken place, or tools and software that are being tested. Examples of this trend include reports of RDM surveys at the University of Pretoria and the Council for Scientific and Industrial Research (CSIR) (Van Deventer & Pienaar 2015), pilot projects at the Cape Peninsula University of Technology (Chiware & Mathe 2015) and the six-month long nationwide digital repository testing of Figshare and Islandora , spearheaded by the Data Intensive Research Initiative of South Africa (DIRISA 2018). An encouraging activity which is indicative of national RDM interest and progress is the establishment of the Network of Data and Information Curation Communities (NeDICC), a South African RDM community of practice, and its short, yet productive, contributions in terms of RDM-centred workshops and meetings (NeDICC 2017).…”
Section: Rdm In South Africamentioning
confidence: 99%
“…As a result, current RDM-related literature tends to report on investigative surveys that have been conducted, pilot projects that have taken place, or tools and software that are being tested. Examples of this trend include reports of RDM surveys at the University of Pretoria and the Council for Scientific and Industrial Research (CSIR) (Van Deventer & Pienaar 2015), pilot projects at the Cape Peninsula University of Technology (Chiware & Mathe 2015) and the six-month long nationwide digital repository testing of Figshare and Islandora , spearheaded by the Data Intensive Research Initiative of South Africa (DIRISA 2018). An encouraging activity which is indicative of national RDM interest and progress is the establishment of the Network of Data and Information Curation Communities (NeDICC), a South African RDM community of practice, and its short, yet productive, contributions in terms of RDM-centred workshops and meetings (NeDICC 2017).…”
Section: Rdm In South Africamentioning
confidence: 99%
“…"(38) Li et al (64) reported providing in-depth data analysis for researchers. Others' services included support and hosting of institutional repositories to store and share researchers' data (30,65), enabling access to datasets and creating data catalogues (66,67), and having dedicated librarians for data management projects (33).…”
Section: Data Management (N=19)mentioning
confidence: 99%
“…4. Cape Peninsula University of Technology (CPUT) Library provides research data services within the e-research environment (Chiware & Mathe, 2016). Limited librarian skill is one of the biggest challenges in offering those services.…”
Section: Benchmarking Of Research Data Servicesmentioning
confidence: 99%